Developmental Biology of the Sea Urchin and Other Marine Invertebrates Methods and Protocols - Carroll, David J.; Stricker, Stephen A. (Methods in Molecular Biology, 2014)
XIV, 347 p. 69 illus., 14 illus. in color.